Hubungan Durasi Dan Intensitas Penggunaan Gadget Dengan Perkembangan Anak Usia Prasekolah Di Wilayah RW 14 - Ziah Afifah Zahra; Susanti Widiastuti; Diah Argarini (Universitas Malahayati, 2022)
ABSTRACT The duration and intensity of the use of gadgets in preschoolers is increasing because gadgets have several interesting features for preschoolers, therefore parents must limit their children so that they do not have a negative impact on the growth of preschoolers. This study aims to determine the relationship between the duration and intensity of gadgets on the development of preschool children in the RW14 Tambun Selatan area. The sampling technique in this study used random sampling. The sample in this study amounted to 58 respondents, the questionnaire on the duration of the use of this gadget has been tested for validity and reliability with a Cronbach's alpha coefficient of 0.850, a questionnaire on the intensity of gadget use with a Cronbach's alpha coefficient of 0.760. The results of the study using Chi-Square a = <0.05 obtained P = 0.013 and 0.01, so H1 is rejected, meaning that there is a relationship between the duration and intensity of using gadgets with the development of preschool children aged 3-5 years. In this study, it can be concluded that most children have good duration when using gadgets and most children are moderate in intensity when playing gadgets. Keywords : Duration, Intensity, Preschool Age Development ABSTRAK Durasi dan intensitas penggunaan gadget pada anak usia prasekolah semakin meningkat disebabkan gadget mempunyai beberapa fitur yang menarik untuk anak usia prasekolah, maka dari itu orang tua harus membatasi anak agar tidak berdampak negatif bagi pertumbuhan anak usia prasekolah. Penelitian ini bertujuan untuk mengetahui hubungan durasi dan intensitas gadget terhadap perkembangan pada anak usia prasekolah diwilayah RW14 Tambun Selatan. Teknik pengambilan sampel pada penelitian ini menggunakan random sampling. Sampel dalam penelitian ini berjumlah 58 responden, kuesioner durasi penggunaan gadget ini telah diuji validitas dan reabilitas dengan nilai koefisien cronbach’s alpha 0.850, kuesioner intensitas penggunaan gadget dengan nilai koefisien cronbach’s alpha 0.760. Hasil penelitian menggunakan Chi-Square a= <0.05 didapatkan P = 0.013 dan P = 0.01, sehingga H1 ditolak artinya ada hubungan durasi dan intensitas menggunakan gadget dengan perkembangan anak usia prasekolah 3-5 tahun. Pada penelitian ini dapat diambil kesimpulan bahwa kebanyakan anak sering durasi nya saat menggunakan gadget dan kebanyakan anak sedang intensitasnya saat bermain gadget. Kata kunci: Durasi, Intensitas, Perkembangan Anak Usia Prasekolah